2015
DOI: 10.1186/s12936-015-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

Airport malaria: report of four cases in Tunisia

Abstract: Four cases of airport malaria were notified for the first time in Tunisia during the summer of 2013. All patients were neighbours living within 2 km of Tunis International Airport. They had no history of travel to malarious countries, of blood transfusion or of intravenous drug use. Although malaria transmission had ceased in Tunisia since 1980, autochthonous infection by local Anopheles mosquitoes was initially considered. However, this diagnostic hypothesis was ruled out due to negative entomological survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…The presence of P. ovale and P. malariae, co-infected with P. falciparum, highlights the impact of those two parasites in asymptomatic and chronic malaria infection. Plasmodium malariae and P. ovale are not usually associated with severe malaria but P. malariae may be responsible for chronic nephrotic syndrome which can be fatal (51), and chronic infections that can last for years (52), even after leaving endemic regions (44,53). Plasmodium ovale is responsible for relapses after months or even years without symptoms due to the presence of hypnozoites (54)(55)(56)(57)(58)(59)(60) and it has been shown to cause severe disease and even death on occasion (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of P. ovale and P. malariae, co-infected with P. falciparum, highlights the impact of those two parasites in asymptomatic and chronic malaria infection. Plasmodium malariae and P. ovale are not usually associated with severe malaria but P. malariae may be responsible for chronic nephrotic syndrome which can be fatal (51), and chronic infections that can last for years (52), even after leaving endemic regions (44,53). Plasmodium ovale is responsible for relapses after months or even years without symptoms due to the presence of hypnozoites (54)(55)(56)(57)(58)(59)(60) and it has been shown to cause severe disease and even death on occasion (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…aegypti into Australia present three main management challenges. They could introduce alleles conferring pyrethroid resistance into the current, pyrethroid-susceptible Australian population and thereby reduce the effectiveness of current control programs; they could bring disease into non-endemic regions (Siala et al, 2015); and they could lead to the establishment of new Australian Ae. aegypti populations outside the current native range in Queensland.…”
Section: Discussionmentioning
confidence: 99%
“…The global epidemiological data reported in 2006 showed that countries mostly affected by airport malaria are in Europe, particularly France (29.2%), Belgium (19.1%) and Switzerland (10.1%), Luxembourg (5.6%), Italy and Germany (4.5%), followed by the UK (15.7%), USA (4.5%), Israel and Australia (1.1%) (Figure 2) [6]. Some cases have also been reported in Tunisia [82]. In the meantime, this epidemiological situation may be changed, with the intensification of international trade.…”
Section: Airport Malaria Epidemiological Profilesmentioning
confidence: 96%